IMPLICATION OF FARMING CULTURAL CHANGES ON FARMHOUSES IN NGADAS VILLAGE - Dian Kartika Santoso; Antariksa Antariksa; Sri Utami (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACTPeople in Ngadas Village have enough time to live in their fields. Therefore, the community build farmhouses to help farming activities. However, as an agricultural landscape, cultivation in Ngadas Village has various dynamics. Changes that occur in the agricultural landscape can be traced through agricultural features formed by the type of agricultural land use. In addition, it can be traced through cultural features that are the result of interactions between human activities and the environment such as farmhouses. Therefore, this study aims to find out the implications of agricultural features on cultural features, especially space in farmhouses. The in-depth interview and observation methods were conducted to identify, then the data obtained were analysed by synchronous and diachronic methods. So, the changes that occur can be determined descriptively. The results of the study show that the culture of shifting cultivation that has become permanent causes the fields to develop along with the changes in the plants that have been planted, the addition of activities and intensity of plant management. More fixed location of the farm more developed and permanent farmhouses has been built. More activities carried out in the fields and the higher intensity of plant management, the wider and more space needed for the fields.Keywords: Agrarian culture, Agricultural landscape, Farmhouses